A Perspective Study on the Sustainability of Action for Change: Sociological Review of Wisdom Training - Ersa Tri Fitriasari (Journal of Applied Sciences and Advanced Technology, 2021)
Leadership Training known as Diklatpim IV, now called Supervisor Leadership Training based on the Regulation of the State Administration Institute No. 15 of 2020 concerning Supervisor Leadership Training (PKP) is a part of developing managerial competence through training. The training produces innovative product in the form of document that will be realized in the organization's unit. The perspective of the sustainability of action for change is an urgent thing to be studied considering the current pandemic conditions which then is expected to have an important role for society and organizations as a means of actualizing implementing action for change based on the commitment of training alumni participants. This study aims to analyze the realization policy towards the perspective of the sustainability of action for change and the utilization of action for change program from a sociological perspective on the sustainability of action for change for the Alumni of Batch 2 Supervisory Leadership Training which consists of 40 participants by combining qualitative approach carried out by survey data, observation, in-depth interview, and quantitative approach with path analysis. The results of the study showed that by designing program based on changes in the mindset and culture set of bureaucratic behavior, namely PDCA (plan, do, check and action), a sociological perspective was very useful in improving and developing management training from the perspective of theory, practical policy, and paradigm change and there was an influence of realization policy variable, orientation variable, and program utilization variable towards action for change.